Banking business in the digital society: foreign experience - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна; Харабара, Владимир; Heorhadze, Oleksandr (Political Science and Security Studies Journal., 2021)
The article examines the world and domestic experience in the use of digitalization in the banking sector. Foreign experience and the reasons for active digitalization in the banking sector of the Ukrainian economy in recent years are analyzed. The study revealed the essence of digital technologies for the development of banking services. The distribution of countries according to the use of digital banking is studied and the leaders of the world banking market are indicated. The analysis of the reasons and segments of distribution of technologies of Internet banking in the period of digital world economy is carried out. The problems and opportunities of digital banking for the world banking business are described and perspective innovative opportunities of banks are formed. It is proved that digital technologies transform the banking activity in the global economy, make it more personalized and general for all devices and applications in which the banking service is implemented. The role of digital banks and their chronology in the global financial system are clarified. It is proved that the key changes in the activities of the banking sector in the context of digitalization should be customer-oriented and ensure the effective development of the domestic banking sector, namely: the formation of a new quality of customer service; development of new and improved existing products, development of new and improved existing channels of banking services; formation of digitally oriented personnel.
Банковский бизнес в цифровом обществе: зарубежный опыт
Keywords: Digital economy; digital banking technologies; banking sector; digitalization; integrated service; digital currency; blockchain